Research policies and strategies for livestock development in developing countries - Ehui, Simeon K.; Fitzhugh, H.A. (German Foundation for International Development, 1995)
This paper presents some thoughts on research policies and strategies to support the Development of the livestock sector in developing countries. Particular emphasis is placed on sub-Saharan Africa. The first section discusses the role of agricultural research in livestock Development and reviews models of agricultural Development and their relevance to the livestock sector. The second section deals with policies and strategies which affect livestock research in developing countries. Research policies and strategies of developing and donor countries as well as regional and international research organizations are specifically addressed. The paper closes in the third section with some concluding qualifications and comments.